Exclusivity and sustainability in the luxury fashion industry : #burnberry - Kleinsmith, Niela, (SAGE Business cases., 2024)
The principle of building and maintaining a reputation of exclusivity has long been acknowledged as the key to the success of luxury brands. The way these ambitions are realized often remains hidden from the public eye. In June 2018, British luxury brand Burberry faced considerable backlash after news surfaced that the brand had burned excess stock worth £28.6 m (USD 37 m) to reportedly safeguard its brand image. Various hashtags circulated, including the viral #Burnberry, publicly calling out the brand for its behavior. The case presents an interesting paradox between a sustainability focus on the one hand, and maintaining exclusivity on the other. Two months after the incident, Burberry gave in to pressure and announced that it would cease its burning practices.